2012
DOI: 10.1021/je3003282
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagrams, Density, and Viscosity for the Pseudoternary System of {Propan-2-yl Tetradecanoate (IPM) (1) + [Tween 80 (21) + Propan-1-ol (22)] (2) + Water (3)}

Abstract: In this work, a microemulsion system composed of propan-2-yl tetradecanoate (IPM) as oil, polyoxyethylene (20) sorbitan monooleate (Tween 80) as surfactant, propan-1-ol as cosurfactant, and water as the hydrophilic phase has been prepared. The pseudoternary phase diagram of {IPM (1) + [Tween 80 (21) + propan-1-ol (22)] (2) + water (3)} at 303.15 K has been constructed at a constant surfactant to cosurfactant mass ratio of 0.5:1. The phase diagram shows the area of microemulsion. Densities and viscosities were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Herein, the average droplet size and size distribution of the [AMIM][Cl]/[AMIM][PF 6 ]/PEGDA/HAPS microemulsions with different amounts of PEGDA were collected and shown in Figure 1. It can be noticed that the size distribution of each PILMs was monodispersed, and the average size ranged from 10–40 nm, which was in accordance with the microemulsion’s nature (<150 nm) [22]. Besides, with the increasing amount of PEGDA, the average size of PILMs increased slightly, and this could be attributed to the droplet structure of PILMs.…”
Section: Resultsmentioning
confidence: 85%
“…Herein, the average droplet size and size distribution of the [AMIM][Cl]/[AMIM][PF 6 ]/PEGDA/HAPS microemulsions with different amounts of PEGDA were collected and shown in Figure 1. It can be noticed that the size distribution of each PILMs was monodispersed, and the average size ranged from 10–40 nm, which was in accordance with the microemulsion’s nature (<150 nm) [22]. Besides, with the increasing amount of PEGDA, the average size of PILMs increased slightly, and this could be attributed to the droplet structure of PILMs.…”
Section: Resultsmentioning
confidence: 85%
“…Microemulsion systems are thermodynamically stable, homogeneous, optically isotropic solutions, consisting of oil, water, and surfactants (cosurfactants). , Ascribing to its typical and distinctive properties, microemulsions have attracted a great deal of attention in different fields of application such as pharmaceutical, cosmetical, and agrochemical formulations over the last few decades. Triglycerides, as the primary components of vegetable oils, have been used as the oil phase in microemulsions. Many researchers have provided substantial information on the formulation, phase diagrams, and microstructure of triglyceride-based microemulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Tween 80/propan-2-yl tetradecanoate/ propan-1-ol/water microemulsion system has also been prepared. [7] It was found that the density would increase along the water dilution line. Also, the viscosity shows a maximum when the composition approaches the phase equilibrium boundary which is relative to the microstructure transition of this microemulsion system.…”
Section: Introductionmentioning
confidence: 99%